Hubungan Antara Aktivitas Fisik Dengan Resiko Jatuh Pada Lanjut Usia Di Desa Jaten Kecamatan Juwiring Klaten - Azizah, Firda Dwi; , Yulisna Mutia Sari, SSt.FT., M.Sc (GRS) (2017)
Background: Elderly decline in physical and social function. The decline in the elderly cause a decrease in physical activity and the risk of falls experienced by the elderly as get older. Risk factors for falls in the elderly influenced by decline of physical activity, muscle strength, and balance. Research Aims: To know correlation of physical activity towards the risk of falling down on elderly at Jaten Village, Juwiring District, Klaten. Research method: The type of research used in this study is descriptive correlative with Cross Sectional approach. The sampling technique used is Purposive Sampling technique with the total samples as many as 75 people. Measurement of physical activity uses Juhendri research questionnare 2016 whereas the measurement of fall of risk uses Tinetti Balance and Gait Evaluation by summing up the score in every number. Research result: Based on Chi-Square test, it is known that p-value score is 0,002 < 0,005 so H0 is declined. It can be interpreted that there is a correlation of physical activity towards the risk of falling down on elderly at Jaten Village, Juwiring District, Klaten. Conclusion: There is a correlation of physical activity towards the risk of falling down on elderly at Jaten Village, Juwiring District, Klaten. Keywords: Physical Activity, Fall Risk, Elderly.